Electrospun Carbon Nanofiber Webs with Controlled Density of States for Sensor Applications. (19th December 2012) - Mao, Xianwen; Simeon, Fritz; Rutledge, Gregory C.; Hatton, T. Alan
<x xml:space="preserve">Abstract</x> Electrospun carbon nanofiber (CNF) webs with controlled density of states (DOS) are synthesized through varying the carbonization conditions to manipulate the concentration of nanosized graphite domains. These materials exhibit adjustable electrochemical activity and biosensitivity: both electron transfer kinetics for various redox systems and direct electron transfer efficiencies with enzymes increase with the DOS of the CNF webs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>